Kartagener Syndrome: A Case Report - AJPRD, Dr Anuradha Kapoor; Dr Mitva Agarwal; Dr Kanika Maheshwari (Asian Journal of Pharmaceutical Research and Development, 2024)
Kartagener syndrome is a rare, autosomal recessive genetic disorder that causes defects in the action of ciliary movement, characterized by clinical triad of situs inversus, chronic sinusitis, and bronchiectasis. We present the case of an 18-year-old male with repeated respiratory infections. He was diagnosed with Kartagener syndrome based on his clinical presentation and imaging features. In patients presenting with recurrent upper and lower respiratory tract infections, Kartagener syndrome should always be kept in mind. The correct diagnosis of this disorder in early life is very important to prevent complications and improve a patient's quality of life.